Report regarding the microbiological quality control of the veterinary pharmaceutical products during 2012 (ro.) - Simona Sturzu; Daniela Tirsinoaga; Ioana Tihulca; Mariana Dumitrache; Alina Draghici (Medicamentul Veterinar)
The microbiological contamination of pharmaceutical products could have major consequences on the physical – chemical characteristics, safety and efficiency of the medicinal products and also on the out of specification products recall-associated costs. Quality control of the pharmaceutical products should be a major objective for both the pharmaceutical industry as well as for the official quality control laboratories and the final results of these tests should provide most accurate data regarding the safety and the efficiency of the controlled pharmaceutical products. This report is presenting the results which were obtained in 2012 in the Microbiological Control Laboratory following the quality control of the products according to their pharmaceutical form and therapeutic class.